PARENTAL INFLUENCE ON MORPHOLOGICAL ACQUISITION IN A TODDLER - Amanda Meirandani; Cici Ulmasitoh; Lisa Aprilia; Muhammad Sadam; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This study examines the morphological development in a 2-year-6-month-old child, K.A., using an interactionist framework. Observations were conducted over one month, revealing that limited exposure to varied linguistic inputs resulted in restricted vocabulary and incomplete sentence formation. Despite K.A.'s responsiveness to communication, the lack of parental engagement, particularly the father's absence, hindered his morphological development. The study found that increased maternal interaction slightly improved K.A.'s use of morphemes and sentence structures, underscoring the crucial role of parental involvement in language acquisition. These findings highlight the importance of enriched linguistic environments and suggest targeted interventions to support early morphological development.